Role of filamin A in the pathogenesis of neuroendocrine tumors and adrenal cancer - Donatella Treppiedi; Rosa Catalano; Federica Mangili; Giovanna Mantovani; Erika Peverelli (Endocrine Oncology, 2023)
Cell cytoskeleton proteins are involved in tumor pathogenesis, progression and pharmacological resistance. Filamin A (FLNA) is a large actin-binding protein with both structural and scaffold functions implicated in a variety of cellular processes, including migration, cell adhesion, differentiation, proliferation and transcription. The role of FLNA in cancers has been studied in multiple types of tumors. FLNA plays a dual role in tumors, depending on its subcellular localization, post-translational modification (as phosphorylation at Ser2125) and interaction with binding partners. This review summarizes the experimental evidence showing the critical involvement of FLNA in the complex biology of endocrine tumors. Particularly, the role of FLNA in regulating expression and signaling of the main pharmacological targets in pituitary neuroendocrine tumors, pancreatic neuroendocrine tumors, pulmonary neuroendocrine tumors and adrenocortical carcinomas, with implications on responsiveness to currently used drugs in the treatment of these tumors, will be discussed.